Pengaruh Kombinasi Polimer HPMC dan PVP terhadap Sifat Fisik Sediaan Patch Ekstrak Pelepah Pisang Ambon (Musa paradisiaca var.sapientum L.) - Yetti Hariningsih; Indri Dwi Rahasasti; Syamsul Ma’arif; Haqoiroh; Kiki Puspitasary (JCPS (Journal of Current Pharmaceutical Sciences), 2025)
The banana plant is one of the traditional plants often used for wound healing. In this study, the sheath of Ambon banana (Musa paradisiaca var. sapientum L.) was used as the active ingredient. The extract of Ambon banana sheath contains secondary metabolite compounds such as flavonoids, saponins, and tannins, which play a role in the wound healing process. The formulation was made in the form of a patch to enhance the effectiveness of active ingredient delivery. This study aims to determine the best patch formulation and analyze the effect of varying concentrations of HPMC and PVP on its physical properties. The patch was prepared using the solvent casting method with three polymer combinations, F1: 2% HPMC and 1% PVP, F2: 1.5% HPMC and 1.5% PVP, F3: 1% HPMC and 2% PVP. The evaluation data were analyzed experimentally and statistically using a one-way ANOVA test. The results showed that the most optimal formula was F1, as it met all the patch testing requirements with the following evaluation data (average ± standard deviation), Weight uniformity 1.1±0.083 (CV<5%), patch thickness: 0.04±0.012 mm (<1 mm),  Folding endurance: 324±6.51 (>300 folds), pH: 5.6±0.025 (range 4.6–8), Moisture absorption: 5.1%±0.182 (<10%). Based on the physical stability test, the results showed that the pH test and weight uniformity had a significance value of ρ > 0.05, indicating no significant differences in each test cycle. Meanwhile, the folding endurance stability test (>300 folds) had a significance value of ρ < 0.05, indicating a significant difference in each test cycle